Comparison of the Ocular Microbiomes of Dry Eye Patients With and Without Autoimmune Disease - Qi, Yun; Wan, Yong; Li, Tianhui; Zhang, Ming; Song, Yu; Hu, Yaguang; Sun, Yining; Li, Li (Frontiers in Cellular and Infection Microbiology, 2021)
Purpose The pathogenesis of dry eye concomitant with autoimmune disease is different from dry eye without autoimmune disease. The aim of this study was to explore the differences in microbiota diversity and composition in dry eye with and without autoimmune disease. Methods Swab samples from the inferior fornix of the conjunctival sac were obtained from dry eyes without autoimmune disease (n=49, dry eye group) and with autoimmune disease (n=38, immdry eye group). Isolated bacterial DNA from swabs were analyzed with 16S rRNA amplicon sequencing. Results Analysis of alpha diversity revealed no significant differences between dry eye and immdry eye subjects. The immdry eye group had a distinct microbial composition compared with the dry eye group. The combination of the Corynebacterium and Pelomonas genera distinguished the immdry eye group from the dry eye group with an area under the curve of 0.73 (95% CI 0.62 to 0.84). For the same bacteria, the correlation between microbe abundance and ocular surface parameters was different in the two groups. In addition, the microbial communities’ functions were altered in the two groups. Conclusions Our study demonstrates changes in the composition and function of the ocular microbiome between the immdry eye and dry eye groups, which suggests the potential pathogenesis is different.